Corrugated Box Production Optimization Using Theory of Constraints (TOC) and DBR - Drum-Buffer-Rope (DBR): Optimasi Produksi Corrugated Box Menggunakan Theory of Constraints (TOC) dan DBR - Drum-Buffer-Rope (DBR) - Budiani, Dian Nissa Fitri; Rochmoeljati, Rr (Indonesian Journal of Innovation Studies, 2025)
General Background: Efficient production processes are critical for manufacturing companies to meet output targets and maintain competitiveness. Specific Background: PT XYZ, a corrugated box manufacturer, is experiencing production delays due to bottlenecks at specific workstations. Knowledge Gap: Previous studies have rarely explored the integrated application of the Theory of Constraints (TOC) and Drum Buffer Rope (DBR) methods specifically within the corrugated box industry. Aims: This study aims to identify bottlenecks and propose improvements in PT XYZ’s production process by applying TOC and implementing the DBR scheduling method. Results: Bottlenecks were found at the Converting (SK-2) and Stitching (SK-4) workstations. Through the five focusing steps of TOC and DBR’s structured flow management using drums, buffers, and ropes, along with extended work hours at bottleneck stations, throughput increased from IDR 5,424,572 to IDR 8,040,195—a 32.53% rise. Novelty: This study presents a comprehensive application of TOC and DBR in the corrugated box sector, combining it with linear programming to optimize resource allocation and bottleneck exploitation. Implications: The findings highlight how TOC and DBR can serve as a strategic framework to improve operational efficiency and output in manufacturing systems constrained by limited capacity. Highlights: Converting and Stitching stations identified as production bottlenecks. Overtime at bottlenecks increased throughput by 32.53%. TOC and DBR integration proved effective in streamlining production. Keywords: Drum Buffer Rope, Corrugated Box, Throughput, Bottleneck, Theory of Constraints